Training on Herbal Soap Preparation From the Extract Combination of Ketepeng Leaf and Sirih Leaf - Nugraha, Sony Eka; Nainggolan, Marline; Keliat, Jane Melita; Maha, Hetty Lendora (Talenta Publisher, 2022)
The problem of sanitation and hygiene is one of the problems faced by many people in Indonesia, especially in the current state of the Covid 19 pandemic. Not to mention the thing that is faced by the people of the Mabar village, Medan Deli sub-district, Medan City is the poor sanitation and hygiene of the community, especially those who live in dense settlements, so it is necessary to campaign for healthy living behaviors, one of which is through counseling on healthy living behaviors in maintaining personal health during the COVID-19 pandemic. and accompanied by training in the manufacture of antibacterial soap to increase public interest and awareness regarding the importance of healthy living. Soap products have developed into a primary need in today's society. These products are used every day by all levels of society, both upper, middle, and lower classes. The partners involved in community service are community groups in Neighborhood IX, Mabar sub-district, Medan Deli sub-district, Medan City. which is quite potential to be developed through a training program for making antibacterial herbal soaps, one of which is made from ketepeng leaves and betel leaves which are widely believed by the community to be effective in curing skin diseases. Several studies have proven that ketepeng and betel leaves have high antibacterial activity which have the potential to be developed into antibacterial soap products.Housewives and teenagers of productive age who are the targets of this service do not yet have productive activities. This training program is expected to provide business opportunities to the community so that it can improve the economy. The soap products produced can be used to meet household needs or can be sold to the surrounding community. With training in making antibacterial herbal soaps, expenses can be reduced and even can improve the household economy.